“Lenghten Life” Operation: Environmental Education, Citzenship and Preservation of Rio Preto - Teles, Rogério de Mesquita; Rocha, Antônio da Paz (European Journal of Sustainable Development, 2017)
This work is the result of a project named “Lenghten Life”, developed since 2010 in São Benedito do Rio Preto, Maranhão, Brazil, involving the Association of Children and Friends of São Benedito and the Association of Young People of Alto Rio Preto. It is a socio-environmental action which promotes the preservation and revitalization of Rio Preto and its main tributary, Rio Mocambo, important sources of water for the population. The operation occurs in three stages: 1) 7 groups of youths performed the river cleaning, quantifying collected garbage, the situation of the streams (tributaries) and environmental crimes. 2) teams sensitized river dwellers on the importance of preservation, pollution dangers and deforestation of the banks, and cataloged extinct species. 3) Plantation and cultivation of native species. The participants volunteered, the action was financed by residents’ donation. In the first year, 132 volunteers participated, collecting 16,442 kilos of garbage and identifying 42 streams (21 “dead”, 09 precarious and 12 good). In 2016, there were 131 participants, the removed garbage reduced to 5,400 kilos, 4 dead streams were revitalized, 5 improved and the others continued with good fluency. Deforestation and predatory fishing decreased. The Project showed efficiency in preserving Rio Preto through environmental education. Keywords: Lenghten Life, environmental education, preservation and revitalization of rivers, São Benedito do Rio Preto – MA (Brazil)